Analysis of Urban Groundwater Quality in Dryland Areas of Kebbi State, Nigeria - Abubakar Usman, Abdulqadir; Wali, Saadu Umar; Shera, Ibrahim Muhammad (The Journal of Experimental Life Science, 2024)
This study aims to assess the physicochemical composition of groundwater in the dryland area of Kebbi State, Nigeria. Groundwater samples were collected from four urban areas – Argungu, Birnin Kebbi, Gwandu, and Kalgo. Forty water samples from deep wells, i.e. boreholes/hand pumps, were obtained and analyzed. Twelve physicochemical parameters were analyzed, and these include Electrical conductivity (EC), pH, Total Dissolved Solids (TDS), Chloride (Cl-), Potassium (K+), Calcium (Ca2+), Iron (Fe3+), Magnesium (Mg2+), Zinc (Zn2+), Cupper (Cu2+) Bicarbonates (HCO3-) and Sodium (Na+). The Weighted Arithmetic Water Quality Index (WAWQI) assessment of groundwater quality for the four urban areas revealed that 45% of the water sources were good quality, 35% were poor quality, and 5% were very poor quality. A 15% were unsuitable for drinking due to the high concentration of EC, TDS, Fe3+, Cu2+, and Ca2+ ions. The physicochemical examination of groundwater from four urban areas showed results that satisfied the WHO drinking water standard. Results from a non-parametric statistical test (Kruskal-Wallis) showed a significant difference in EC and TDS are significant at < 0.001 in the groundwater of Gwandu, while no significant differences exist in the physicochemical parameters of Argungu, Birnin Kebbi, and Kalgo. Pearson’s correlation analysis indicated that rock weathering controls groundwater quality primarily. However, correlations between TDS and other physicochemical parameters are indications of anthropogenic contributions to groundwater pollution in the study area.  The overall assessment of the Water Quality Index in the study area indicates that groundwater needs treatment, proper maintenance, and compliance with the world standard. Keywords: Groundwater, Physicochemical parameters, Water quality, Weighted Arithmetic Water Quality Index (WAWQI).